Bridge Structural Health Monitoring Using Mobile Sensor Networks - Amin, Fouad (2022)
A Master of Science thesis in Civil Engineering by Fouad Mostafa Fouad Amin entitled, “Bridge Structural Health Monitoring Using Mobile Sensor Networks”, submitted in December 2022. Thesis advisor is Dr. Mohammad AlHamaydeh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).